The Use of Positive and Negative Politeness Strategies to Express Request in English and Armenian Cultures - Yaghubyan, Marine (Armenian Folia Anglistika, 2019)
Politeness is an indispensable topic in pragmatics. The standard of politeness may vary from group to group, from situation to situation and even from person to person. In pragmatics the principle of politeness is related to the choices that are made in the language usage, the linguistic expressions that give people space and express a friendly attitude.The present article focuses on the examination and comparison of positive and negative politeness strategies to express request in English and Armenian cultures. The analysis shows that in Armenian culture positive politeness is highlighted. On the contrary, in English culture requests are made within negative politeness strategies.
Keywords: positive politeness; negative politeness; request; culture; positive face; negative face; politeness strategies